The Questions of Compulsory Organ Donation: The Trolley Dilemma - A Discussion From Ethical, Legal, and SocialEconomical Perspectives - Khoa Tran; Anh Tuyet Nguyen (Institute of Medico-legal Publications Pvt Ltd, 2021)
The Covid-19 pandemic has inflicted disastrous damages on various aspects of human lives, especially the healthcare sector. The shortage of beds, medical staff, and other facilities in hospitals posed an acute dilemma over who should be given precedence in the treatment process and whether a more seriously ill person should sacrifice for people with less severe illness. With an interpretative approach, this short research article discusses the above questions by using compulsory organ donations as a proxy. After evaluating the compulsory organ donation from the ethical aspect, researchers then dig into the issue from legal and socioeconomic perspectives. The authors are convinced by Kant and Nozick’s proposals on ethics and justice regarding organ donation and patient sacrifice. The research also found out that the problem is not merely limited to the question of morality but also extended to an opt-out system for ensuring social welfare. Finally, the paper encourages medical practitioners, legislators, and social activists to make decisions about medical-legal issues based on interdisciplinary views.